Patent power in biomedical innovation: Technology governance in biomodifying technologies. (24th July 2022) - Bicudo, Edison; Morrison, Michael; Li, Phoebe; Faulkner, Alex; Webster, Andrew; Mourby, Miranda; Kaye, Jane
Abstract: Biomedical innovation is often rewarded by exclusive proprietary rights such as patents. In the case of gene editing, induced pluripotent stem cells, and three‐dimensional (3D) bioprinting (here described as biomodifying technologies), the limitations of the patent system come into stark relief, generating both technical and political doubts. Generally, political and technological limitations are supposed to be solved with so‐called good governance, based on some principles. We focus on three of such governance principles (participation, accountability, and transparency) to show how they have been weakened, instead of strengthened, by the current patent system. We demonstrate that although patent applications are submitted by both public and private players, the latter have imposed a growing dominance in gene editing, induced pluripotent stem cells, and 3D bioprinting, disseminating their aggressive and exclusive strategies. As a consequence, a logic of experimentality tends to prevail where the three fundamental governance principles fail to be enacted.